2019
DOI: 10.1371/journal.pone.0213437
|View full text |Cite
|
Sign up to set email alerts
|

Utility of EBUS-TBNA in PET-positive mediastinal lymph nodes in subjects with extra-thoracic malignancy

Abstract: Background/AimPatients with primary extra-thoracic malignancy (ETM) often have hyper-metabolic mediastinal lymph nodes (HM-MLN) in the PET-scan done for initial staging or post treatment follow-up. There is scant data on the etiology of HM-MLN in such patients, which can also be due to non-malignant causes. We used endobronchial ultrasound (EBUS) guided sampling to determine the etiology of HM-MLN in patients with ETM and study the relationship between PET-SUV values and a diagnosis of malignancy in this popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The frequency of granulomatous MLN in patients with ETM differs between 5.2% and 36.9% 1,8–12 . It was 13.8% in our study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The frequency of granulomatous MLN in patients with ETM differs between 5.2% and 36.9% 1,8–12 . It was 13.8% in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…Discriminating between granulomatous inflammation and malignancy based on CT and/or PET‐CT findings is difficult. Both are FDG avid 8 and SUV values are similar 11 . However, unilateral or asymmetrical enlargement, presence of coalescence, blurred margins, or necrosis suggest metastasis, lymphoma, or tuberculosis 19,20 .…”
Section: Discussionmentioning
confidence: 98%
“…Primary lung cancer with nodal involvement accounts for the majority of mediastinal and hilar lymphadenopathy cases[ 20 ], but Mehta et al [ 13 ] showed a high frequency of benign diagnoses. EBUS-TBNA is considered safe and feasible for tissue sampling with access to both mediastinal and hilar lymph nodes, which is recommended by both the American College of Chest Physicians and European Society of Thoracic Surgeons in primary lung cancer[ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…EBUS-TBNA is also of value for the diagnosis of mediastinal lymphoma[ 11 ]. In clinical practice, EBUS-TBNA could be considered the first-line examination for suspicious mediastinal lymph nodes in patients with extrathoracic cancer, preventing surgery in 50% of them[ 12 ]; in contrast, the use of EBUS-TBNA in intrathoracic lymphadenopathy in patients with extrathoracic solid organ malignancy is a relatively less investigated topic[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported mediastinal and hilar LN showing high metabolic activity associated with sarcoidosis and tuberculosis in patients with ETM (6). There can be a high level of confusion between a primary tumor and mediastinal and hilar LN with increasing activity, or which emerge as a response to malignancy treatment.…”
Section: Introductionmentioning
confidence: 95%